Enhancing Internet Search Abilities for People with Intellectual Disabilities in Sri Lanka - Arachchi, T.K.; Sitbon, Laurianne; Zhang, Jinglan; Gamage, Ruwan; Hewagamage, Priyantha (ACM, 2021)
This article presents how young adults with intellectual disability (ID) from Sri Lanka, who had not previously used the Internet, interacted with Google search while enhancing their web search abilities throughout three web search workshops. Considering the little attention paid on the learning needs of people with ID in the current offering web search learning tools, we iteratively developed a suite of learning tools to support our participants when they need help in the web search workshops. We employed an iterative participatory approach, with observations and semistructured interviews, to reflect on how to design eLearning tools that enhance the participants’ interactions with websearch. The qualitative thematic analysis resulted in five distinct themes on strategies to support, build on and develop the abilities of a young adults with intellectual disabilities as they engage with Google search in their native language: application of existing abilities, basic skills to match with learning needs, conceptual understanding, animations to facilitate visual memory, and promoting active engagement. These themes will be a starting point for understanding participants’ learning needs and behavior on web search, which would be important for future research on learning support as well as on software design.
Keywords: Web search; Accessible design; Human-computers interface interaction; People with intellectual disabilities